2023
DOI: 10.22175/mmb.12473
|View full text |Cite
|
Sign up to set email alerts
|

American Meat Science Association Guidelines for Meat Color Measurement

Abstract: Meat color is an important aspect of consumer’spurchase decisions regarding meat products. Perceived meat color results from the interaction of light, a detector(i.e. human eye), and numerous factors that are both intrinsic and extrinsic tothe muscle which influence the chemical state of myoglobin.  The complex nature of these interactions dictatesthat decisions regarding evaluations of meat color be made carefully, and thatinvestigators have a basic knowledge of the physical and chemical fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(43 citation statements)
references
References 137 publications
(151 reference statements)
2
40
0
1
Order By: Relevance
“…The hue angle indicates the hue of a color and is expressed in degrees: 0 • would be red, 90 • yellow, 180 • green, and 270 • blue. According to King et al (2023), the hue angle is very useful to indicate shifts in color over time and is thus well suited to follow discolorations. Chroma is an indicator for the saturation and therefore refers to the degree of vividness of a color.…”
Section: Instrumental Colormentioning
confidence: 99%
See 4 more Smart Citations
“…The hue angle indicates the hue of a color and is expressed in degrees: 0 • would be red, 90 • yellow, 180 • green, and 270 • blue. According to King et al (2023), the hue angle is very useful to indicate shifts in color over time and is thus well suited to follow discolorations. Chroma is an indicator for the saturation and therefore refers to the degree of vividness of a color.…”
Section: Instrumental Colormentioning
confidence: 99%
“…As the color of meat is largely determined by the relative amounts of the three major pigments deoxymyoglobin, metmyoglobin, and oxymyoglobin, reflectance measurements and visible absorption characteristics can be used to detect the amount and chemical state of myoglobin (Warner, 2014). For example, the ratio or difference between the reflectance percentage at 630 and 580 nm (R630/R580) is a parameter for the redness of meat samples and is typically used to measure changes in fresh meat color during display (King et al, 2023). Karamucki et al (2017) reported high correlations between changes in the relative levels of metmyoglobin and color change based on the absorbance of wavelengths of 540 and 505 nm and concluded that these parameters for color changes are more useful in the assessment of pork quality than the redness Δa* and hue angle Δh • .…”
Section: Instrumental Colormentioning
confidence: 99%
See 3 more Smart Citations